Defining Content for a Competency-based (CanMEDS) Postgraduate Curriculum in Ambulatory Care: A Delphi Study (Canadian Medical Education Journal, 2012)
Background: Ambulatory training in internal medicine has been noted to be dysfunctional and inadequate. In this study, we developed a set of competency-based outcomes specific to ambulatory care to guide the design, implementation and evaluation of instructional events to ensure that societal needs are addressed. Methods: In 2007 a Delphi technique was used to reach consensus and define the priorities for competency-based training in ambulatory care for internal medicine residents. Four groups of stakeholders in Canada participated: program directors, members of the Canadian Society of Internal Medicine, recent graduates, and residents. Results: Two rounds of the Delphi process were required to reach consensus on a set of sixty competency-based educational objectives in ambulatory care that were classified under the CanMEDS roles. The inclusion of recent graduates in this study resulted in the addition of non-clinical topics that would have otherwise been missed, falling under roles historically viewed as being challenging to teach and evaluate (Manager, Health Advocate). Conclusion: This study is the first time a Delphi-process has been used to define the priorities for ambulatory care training in internal medicine under a competency-based framework. The resulting compendium of competency-based objectives provides a foundation from which educators can design, evaluate and modify existing training experiences.